Saintific Method In Reading Comprehension - Caltira Rosiana (STKIP PGRI Nganjuk, 2019)
Experimental research was conduct toward this study. The researcher doing this research as the continue research from last study, to know the effectiveness of using Saintific Method for others subject. There are any differences between student’s reading comprehension skill before and after being taught by using Saintific Method in the eleventh grade of Math and CIVICs Students. So, the Saintific Method is effective to teaching student’s reading comprehension. Based on the observation in the experimental class for non English- Students was good result. It shows the students get score average in pre-test 66,66 and post-test was 80,55.